Kulturelle Transformationsprozesse in der Geldgeschichte des vorislamischen Asien. Iran – Baktrien – Indien - Matthias Hoernes (Historia.scribere)
The following paper examines processes of exchange and transfer of cultural patterns, forms of representation and religious concepts via commerce and monetary systems. It focuses on the monetary history of ancient Iran, Bactria as well as Northwestern India. Furthermore it addresses also the phenomena of continuity and discontinuity which occur in the course of change in sovereignty, namely in the Seleucid, Arsacid and Sasanid era of Iran, under the reign of Greco-Bactrian and Indo-Greek kings in Bactria and in the Indian Kushan Empire.